Towards equitable surgical systems: development and outcomes of a national surgical, obstetric and anaesthesia plan in Tanzania. Issue 2 (16th April 2019) - Citron, Isabelle; Jumbam, Desmond; Dahm, James; Mukhopadhyay, Swagoto; Nyberger, Karolina; Iverson, Katherine; Akoko, Larry; Lugazia, Edwin; D'Mello, Brenda; Maongezi, Sarah; Nguhuni, Boniface; Kapologwe, Ntuli; et al.
Abstract: Despite emergency and essential surgery and anaesthesia care being recognised as a part of Universal Health Coverage, 5 billion people worldwide lack access to safe, timely and affordable surgery and anaesthesia care. In Tanzania, 19% of all deaths and 17 % of disability-adjusted life years are attributable to conditions amenable to surgery. It is recommended that countries develop and implement National Surgical, Obstetric and Anesthesia Plans (NSOAPs) to systematically improve quality and access to surgical, obstetric and anaesthesia (SOA) care across six domains of the health system including (1) service delivery, (2) infrastructure, including equipment and supplies, (3) workforce, (4) information management, (5) finance and (6) Governance. This paper describes the NSOAP development, recommendations and lessons learnt from undertaking NSOAP development in Tanzania. The NSOAP development driven by the Ministry of Health Community Development Gender Elderly and Children involved broad consultation with over 200 stakeholders from across government, professional associations, clinicians, ancillary staff, civil society and patient organisations. The NSOAP describes time-bound, costed strategic objectives, outputs, activities and targets to improve each domain of the SOA system. The final NSOAP is ambitious but attainable, reflects on-the-ground priorities, aligns with existing health policy and costs an additional 3% of current healthcare expenditure. Tanzania is the third country to complete such a plan and the first to report on the NSOAP development in such detail. The NSOAP development in Tanzania provides a roadmap for other countries wishing to undertake a similar NSOAP development to strengthen their SOA system.